PELATIHAN DESAIN MEDIA DENGAN APLIKASI CANVA UNTUK SISWA MADRASAH ALIYAH MA'ARIF NU PEKANBARU - Zamsuri, Ahmad; Susandri, Susandri; Pane, Eddissyah Putra; Feldiansyah, Feldiansyah; Fajrizal, Fajrizal; Herlina, Sari (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: The Canva application is an application that can be used in creating banner designs. With the utilization and development of techniques in making banner designs. In this case, the use of attractive and appropriate media in the process of making training banners will have a positive impact that will have the potential to greatly improve students' ability to create banners with the Canva application. Students and students really need knowledge in making media design with the aim of providing provisions in making media design even though students at Madrasah Aliyah Ma'arif NU Pekanbaru are quite many who want trainings to improve students' soft skill knowledge. Community Service offers a solution in the form of media design making training with the Canva application for students of Madrasah Aliyah Ma'arif NU Pekanbaru. Where this program is expected to be a forum and inspiration for students to increase their knowledge in making Media Design with the canva application. Where this program is expected to be able to be a forum and inspiration for students to be able to increase their knowledge in making Media Design with the great canva application that students and students of Madrasah Aliyah Ma'arif NU Pekanbaru hope for. As a speaker, he provided socialization and at the same time assistance on how to make Media Design with an interesting and certainly very useful application for students of Madrasah Aliyah Ma'arif NU Pekanbaru. Keyword: Media Design, Canva, Students of Madrasah Aliyah Ma'arif NU Pekanbaru  Abstrak: Aplikasi canva merupakan aplikasi yang dapat digunakan dalam pembuatan desain spanduk. Dengan pemanfaatan dan pengembangkan teknik dalam pembuatan desain spanduk. Dalam hal ini, pemanfaatan media yang menarik dan tepat guna dalam proses pembuatan spanduk pelatihan akan memiliki dampak positif yang akan sangat berpotensi meningkatkan kemampuan siswa dalam membuat spanduk dengan aplikasi canva. Para siswa dan siswi sangat membutuhkan pengetahuan dalam membuat desain media dengan tujuan memberikan bekal dalam pembuatan desain media walaupun siswa di Madrasah Aliyah Ma'arif NU Pekanbaru cukup bayak yang menginkan pelatihan-pelatihan untuk meningkatkan pengetahuan softskill siswa. Pengabdian Kepada Masyarakat menawarkan solusi berupa pelatihan pembuatan desain media dengan aplikasi canva untuk siswa Madrasah Aliyah Ma'arif NU Pekanbaru. Di mana program ini diharapkan mampu menjadi wadah dan inspirasi bagi para siswa dapat menambah pengetahuan dalam membuat Desain Media dengan aplikasi canva besar harapan siswa dan siswa Madrasah Aliyah Ma'arif NU Pekanbaru. Sebagai pemateri memberikan sosialisasi dan sekaligus pendampingan mengenai bagaimana pembuatan Desain Media dengan aplikasi canva yang menarik dan pastinya sagat dapat bermanfaat bagi siswa Madrasah Aliyah Ma'arif NU Pekanbaru. Kata kunci: Desain Media, Canva, Siswa Madrasah Aliyah Ma'arif NU Pekanbaru